Analysis of the factors that influence the student’s performance of uniform high school and technical vocational school in the subjects of statistics - Παπακωνσταντίνου Ευάγγελος; Γιαλαμάς Βασίλης; Καραγεώργος Δημήτρης Λ. (SPOUDAI Journal of Economics and Business, 2006)
In the present research, an attempt was made to find the factors that determine the level of achievement of the students in the subject of Statistics. This subject is taught in the second (upper) level of Secondary Education (S.E.), viz. in the third (last) grade of Uniform High School (U.H.S.) and in the first grade of the Technical Vocational School -T.V.S. (in the field of the Economy and Management). Furthermore, the achievement of the students in Statistics was examined according to subject matter. Based on the findings of this research, some proposals have been formulated for the better instruction of the subject. In Greece, S.E. is comprised of the first level which corresponds to the Middle or Junior High School and the second level which includes the U.H.S. and the T.V.S. The length of study for each level is three years.